Soil nematode community assembly in a primary tropical lowland rainforest - Hou, Weichen; He, Mengfei; Qi, Yanwen; Liu, Tiedong; Luo, Jinhuan (Frontiers in Ecology and Evolution, 2022)
More than half of the world's tropical lowland rainforests have been lost due to conversion to agricultural land (such as rubber plantations). Thus, ecological restoration in degraded tropical lowland rainforests is crucial. The first step to restoration is restoring soil functioning (i.e., soil fertility, carbon, and nitrogen cycling) to levels similar to those in the primary tropical lowland rainforest. This requires understanding soil nematode community assembly in primary tropical lowland rainforest, which has never been explored in this habitat. In this study, we measured species compositions of plant and soil nematode communities and soil characteristics (pH, total and available nitrogen, phosphorus, and soil water content) in a primary tropical lowland rainforest, which is located on Hainan Island, China. We performed two tests (the null-model test and distance-based Moran's eigenvector maps (MEM) and redundancy analysis-based variance partitioning) to quantify the relative contribution of the deterministic (abiotic filtering and biotic interactions) and stochastic processes (random processes and dispersal limitation) to the soil nematode community. We found that a deterministic process (habitat filtering) determined nematode community assembly in our tropical lowland rainforest. Moreover, soil properties, but not plant diversity, were the key determinants of nematode community assembly. We have, for the first time, managed to identify factors that contribute to the nematode community assembly in the tropical lowland rainforest. This quantified community assembly mechanism can guide future soil functioning recovery of the tropical lowland rainforest.